1996
DOI: 10.1074/jbc.271.16.9863
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of the Clearance Function of Type C Receptors of Natriuretic Peptides

Abstract: Receptor-mediated endocytosis is the cellular mechanism by which type C receptors of natriuretic peptides exert their clearance function. In the present work, performed in recombinant Chinese hamster ovary cells stably transfected with wild type or mutated human kidney C receptors, we determined net endocytic rates (ER) of C receptor-ligand complexes, lysosomal hydrolysis of ligand (125I-labeled native atrial natriuretic factor, ANF1-28), and receptor recycling. Equilibrium ligand binding, immunocytochemistry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…Our results cannot be attributed to a putative defect of CHO cells to effectuate receptor endocytosis or to an intrinsic decrease in receptor affinity in these cells. Indeed, we have previously shown that clearance receptors of natriuretic peptides stably transfected into CHO cells undergo robust endocytosis and have very low receptor-ligand dissociation at 37°C (12). Thus, the lack of appreciable endocytosis and the rapid receptorligand dissociation of native GCA in primary culture cells or of GCA stably transfected into CHO cells are likely to reflect the dynamics of this receptor under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results cannot be attributed to a putative defect of CHO cells to effectuate receptor endocytosis or to an intrinsic decrease in receptor affinity in these cells. Indeed, we have previously shown that clearance receptors of natriuretic peptides stably transfected into CHO cells undergo robust endocytosis and have very low receptor-ligand dissociation at 37°C (12). Thus, the lack of appreciable endocytosis and the rapid receptorligand dissociation of native GCA in primary culture cells or of GCA stably transfected into CHO cells are likely to reflect the dynamics of this receptor under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Fate I-ANP-(1-28) in intact cells was determined by chase experiments as previously described (10,12). Briefly, CHO cells stably transfected with GCAWT or mutant GCA receptors were grown to near confluence in six-well plates.…”
Section: Cell Culture and Stable Transfection Of Recombinant Receptors-mentioning
confidence: 99%
See 2 more Smart Citations
“…The clearance receptor lacks the GCase domain and is not a GCasecoupled signaling receptor (18). Rather, the receptor mediates metabolic clearance of natriuretic peptides from the circulation (19,20). Nevertheless, the clearance receptor has considerable sequence homology with the corresponding extracellular and transmembrane regions of the ANP receptor and, consequently, is expected to have a similar overall structure.…”
mentioning
confidence: 99%